1970
DOI: 10.1002/j.2164-4918.1970.tb03374.x
|View full text |Cite
|
Sign up to set email alerts
|

Need for approval and counseling outcomes

Abstract: The intent of this study was to determine the effects of a clients' need for approval on the outcomes of counseling. The expectation was that clients who have a high need for approval by others would cooperate more with the counseling process and would more often be successful in the sense of being rehabilitated. The Marlowe‐Crowne Social Desirability Scale was administered to 167 applicants at a state rehabilitation agency immediately after the initial interview. It was hypothesized that successfully rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1977
1977

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Significant people in the practicum and internship sequence, such as professors and agency supervisors, should be able to provide reinforcers to shape desirable counseling behavior. This assumption is supported by MacGuffie, Jorgensen, and Janzen (1970) who demonstrated that graduate social work students modeled after their field instructors.…”
Section: Rationalementioning
confidence: 84%
“…Significant people in the practicum and internship sequence, such as professors and agency supervisors, should be able to provide reinforcers to shape desirable counseling behavior. This assumption is supported by MacGuffie, Jorgensen, and Janzen (1970) who demonstrated that graduate social work students modeled after their field instructors.…”
Section: Rationalementioning
confidence: 84%